To Admit or Not to Admit on the Morning of Surgery: Patients' Perspectives on Day of Surgery Admission. Issue 3 (March 2013) - Harries, RL; Bradshaw, CA; Jones, EA; Lewis, P
Patient experience of day of surgery admission (DOSA) has not been studied in depth. Over a one-month period a questionnaire was given to consecutive patients prior to their surgery to obtain their perspective on the desirability of DOSA and to examine whether other factors influenced this decision. 149 patients participated; across all age groups there was a statistically significant difference in preferring DOSA (p=0.01).